PERAN SEKTOR PERKEBUNAN DALAM PEREKONOMIAN SUMATERA UTARA - Ina Namora Putri (Quantitative Economics Journal, 2014)
The plantation are one of the sectors that are considered able to survive and make asignificant contribution in the post-crisis economic recovery. The purpose of thisstudy was to analyze the relationship plantation sector and the impact of theplantation sector gross output, labor and households in the economy in NorthSumatra. In measuring and analyzing the tables used are Social AccountingMatrix (SAM) or a Social Accounting Matrix (SAM) of North Sumatra. Inconnection table SAM North Sumatra province is not yet available, therefore inthis study was built tables SAM 1995 and 2009, the structure refers to theprocessed products which have been built by Ginting (2006). Based on the analysis it appears that the role of plantations in North Sumatra as indicated by the results obtained have power spread index greater (>1) means the plantation sector has the ability to attract growth in upstream sectors (backward linkages). In addition, this sector has a multiplier of gross output of more than three, which means when in the injection of one unit in this sector, then the resulting output has tripled over the breadth of the effect of forward and backward. And based on the order of rank, occupies five large estates.